Memory, Trauma, and Identity - Eyerman, Ron.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This volume brings together Ron Eyerman's most important interventions in the field of cultural trauma and offers an accessible entry point into the origins and development of this theory and a framework of an analysis that has now achieved the status of a research paradigm. This collection of disparate essays, published between 2004 and 2018, coheres around an original introduction that not only provides a historical overview of cultural trauma, but is also an important theoretical contribution to cultural trauma and collective identity in its own right. The Afterword from esteemed sociologist Eric Woods connects the essays and explores their significance for the broader fields of sociology, behavioral science, and trauma studies.
1: Introduction: Identity, Memory, and Trauma -- 2: The Past in the Present: Culture and the Transmission of Memory -- 3: Intellectuals and Cultural Trauma -- 4: The Assassination of Harvey Milk -- 5: Social Theory and Cultural Trauma -- 6: The Worst Was the Silence: The Unfinished Drama of the Katyn Massacre -- 7: Cultural Trauma, Collective Memory and the Vietnam War -- 8: Perpetrator Trauma and Collective Guilt -- 9. Conclusion: Ron Eyerman and the Study of Cultural Trauma.
Keywords: Sociology; Culture; Culture -- Study and teaching; Sociological Theory; Sociology of Culture; Cultural Studies